2003
DOI: 10.1080/00014788.2003.9729647
|View full text |Cite
|
Sign up to set email alerts
|

Audit fee determinants and auditor premiums: evidence from the micro-firm sub-market

Abstract: Despite the growing literature on the market for audit services, to date no study has examined the determinants of audit fees for the smallest auditees in the market. This study therefore provides some new theory and evidence on the determinants of the audit fees of micro-firms operating in the UK manufacturing sector. A key finding of the study is that in the highly competitive market under consideration, independent small auditees willingly paid a premium to be audited by a mid-tier or a (then) Big Six audit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
1
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(64 citation statements)
references
References 44 publications
6
53
1
4
Order By: Relevance
“…These models, and others (e.g. Simunic, 1980;Simon and Francis, 1988;Pong and Whittington, 1994;Gregory and Collier, 1996;McMeeking et al, 2003a;Peel and Roberts, 2003), have demonstrated relatively high explanatory power and have been robust across different samples, time periods, and countries, and to sensitivity analysis for model misspecification. Although Pong and Whittington ( 1994) argue that many audit fee models used in prior research are mis-specified, this seems to have had relatively little impact on the explanatory power and predictive power of the models."'…”
Section: Research Methods and Datamentioning
confidence: 97%
See 1 more Smart Citation
“…These models, and others (e.g. Simunic, 1980;Simon and Francis, 1988;Pong and Whittington, 1994;Gregory and Collier, 1996;McMeeking et al, 2003a;Peel and Roberts, 2003), have demonstrated relatively high explanatory power and have been robust across different samples, time periods, and countries, and to sensitivity analysis for model misspecification. Although Pong and Whittington ( 1994) argue that many audit fee models used in prior research are mis-specified, this seems to have had relatively little impact on the explanatory power and predictive power of the models."'…”
Section: Research Methods and Datamentioning
confidence: 97%
“…Model specification is very important in audit fee studies (Pong and Whittington, 1994;McMeeking et al, 2003b;Peel and Roberts, 2003). Accordingly, we run a number of alternative models to examine how robust our main results are.17 Pong andWhittington (1994: 1075) advocate a quadratic model where sales, assets, and their squared terms appear.…”
Section: Sensitivity Testsmentioning
confidence: 92%
“…Hay and Davis (2002) find that firms seeking higher quality audits do so for signaling reasons. Peel and Roberts (2003) find that small firms willingly hire higher priced audit firms to send signals of operations and earnings quality to investors. Danielson et al, (2009), suggest that because REITs can derive benefits from hiring high quality auditors, doing so to convey financial transparency can be an important aspect of REITs' capital structure mechanisms.…”
Section: 2financial Transparency and Auditor Qualitymentioning
confidence: 99%
“…9 Determinants studied range from the adoption of International Financial Reporting Standards (Kim, Liu, and Zheng 2012;De George, Ferguson, and Spear 2013) to social capital (Jha and Chen 2015), and they use samples that span U.S. and international firms, industries, and various client sizes (e.g., Peel and Roberts [2003] and Francis and Simon [1987] study audit fees among smaller clients). Although to a lesser degree, audit fees among government organizations have also been studied, with some results consistent with the for-profit audit fee literature.…”
Section: Development Of Hypothesesmentioning
confidence: 99%